Training Need Analysis for PT Krakatau Sarana Infrastruktur Employees - Zahirah, Fairuza; Hartono, Arif; Suhartini, Suhartini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Nowadays, changes occur very quickly, especially in the field of technology, which requires companies to be able to adapt to these changes. Training and development is one of the most effective ways to continuously improve the knowledge and skills possessed by employees. When conducting training, of course the company must do it correctly so that it is in line with the company's goals and is on target. Training needs analysis is one of the most important stages before holding training because this stage determines which employees will take part in the training and what kind of training will be held. This research uses a qualitative approach using a case study design to obtain in-depth data. Data collection techniques for this research used interview, observation and documentation methods. The primary data source comes from interviews with 3 sources and observations and the secondary data source comes from the employee competency GAP report as the main data for training need analysis. The results of this research show that there are still several employees whose competencies do not meet the requirements required by the company. Therefore, companies should be able to continue to update employee competency GAP reports so that training needs analysis can continue to be up to date and can carry out training according to targets and objectives.